KARNAVAL SOUND HOREG: MENGUNGKAP FENOMENA KARNAVAL SOUND SYSTEM DI MALANG - Yuriananta, Renda (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
The sound horeg phenomenon that has emerged across Malang Raya reflects a unique form of youth social expression shaped by digital media, popular culture, and the dynamics of local identity. This study aims to reveal the social meanings, cultural contexts, and societal as well as governmental responses to this phenomenon. A qualitative-descriptive method was employed, utilizing a digital ethnography approach and field observations at several central locations of sound horeg activities. The findings indicate that sound horeg is not merely an eccentric or deviant behavior but also a symbolic communication strategy used by young people to express existence and solidarity in public spaces. However, tensions arise when such expressions clash with social norms, safety, and public order. Therefore, educational and cultural approaches are needed to channel the expressive energy of the youth toward more constructive purposes. This study contributes to contemporary cultural studies and character education in the digital era, particularly in understanding the transformation of values and social behavior among urban Indonesian youth Keywords: sound horeg, social expression, popular culture, youth identity, Malang Raya